2017
DOI: 10.1158/2326-6066.cir-16-0216
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Derived α-Fetoprotein Directly Drives Human Natural Killer–Cell Activation and Subsequent Cell Death

Abstract: Hepatocellular carcinoma (HCC) patients with reduced natural killer (NK)-cell numbers and function have been shown to have a poor disease outcome. Mechanisms underlying NK-cell deficiency and dysfunction in HCC patients remain largely unresolved. α-Fetoprotein (AFP) is an oncofetal antigen produced by HCC. Previous studies demonstrated that tumor-derived AFP (tAFP) can indirectly impair NK-cell activity by suppressing dendritic cell function. However, a direct tAFP effect on NK cells remains unexplored. The pu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 49 publications
0
25
0
Order By: Relevance
“…A recent study also indicates AFP may exert dual effects on NK cells functions in a direct manner. Short-term exposure to AFP induces IL-2 hyperresponsive phenotype NK cells, accompanied with elevated secretion of IL-1β, IL-6 and TNF-α [82]. These pro-inflammatory cytokines were associated with a low recurrence rate and a prolonged overall survival (OS) of HBV-related HCC patients [83].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study also indicates AFP may exert dual effects on NK cells functions in a direct manner. Short-term exposure to AFP induces IL-2 hyperresponsive phenotype NK cells, accompanied with elevated secretion of IL-1β, IL-6 and TNF-α [82]. These pro-inflammatory cytokines were associated with a low recurrence rate and a prolonged overall survival (OS) of HBV-related HCC patients [83].…”
Section: Introductionmentioning
confidence: 99%
“…DC derived from monocytes cultured in the presence of AFP (both tAFP and nAFP) stimulated T cells with a lower level of proliferation, in both a mixed lymphocyte reaction (MLR), and in an influenza-specific T cell recall response assay [3]. More recently, we found that AFP can impact the ability of human dendritic cells (DC) to stimulate NK cells [4], resulting in altered cytokine production and decreased NK cell viability.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst prospective validation of this finding is needed, this association may in part explain the better prognosis of patients with HCC who do not secrete AFP. Recent in vitro studies have demonstrated that tumour-derived AFP can directly impair natural killer (NK) cell activation and viability [ 32 ], indirectly impair NK cell activity through suppression of dendritic cell function [ 33 ], and induce aberrant dendritic cell differentiation with consequential reduction in the secretion of inflammatory cytokines and chemokines and limited T cell activation [ 34 , 35 ]. Thus shifting the balance towards a high NLR in the presence of AFP.…”
Section: Discussionmentioning
confidence: 99%